(untitled) (Journal of Applied Learning and Teaching, 2020)
Interprofessional learning (IPL) is vital for developing work-ready health graduates and enhancing outcomes of people living with persistent pain. Our aim was to pilot an authentic IPL workshop on persistent pain in an Exercise Physiology Clinic. We also sought to explore the application of Adult Learning and Social Identity theories in understanding learning outcomes. Thirty students from five health disciplines participated in a half-day workshop on IPL and persistent pain, facilitated by multidisciplinary staff. Workshop activities included authentic, simulated case studies and problem-based learning. A mixed-methods, pre-post survey showed significant increases in students’ confidence in understanding their own and others’ discipline roles in managing persistent pain (p < 0.001), readiness for IPL (p = 0.046) and self-efficacy (p < 0.001). These increases were supported by qualitative outcomes, which were mapped onto Adult Learning and Social Identity theory. A preliminary conceptual framework was developed incorporating proposed learning mechanisms This innovative workshop, delivered through an Exercise Physiology clinic, formed an effective learning environment, increasing understanding of discipline roles generally and in the pain context. It led to a preliminary conceptual framework to understand learning processes underpinned by theory. There is potential for application of this IPL approach for other chronic conditions. Persistent (or chronic) pain, is defined as pain experienced every day for three months or more in the previous six-month period and affects at least one in five Australians (Access Economics, 2007). Persistent pain is associated with ageing, lower socio-economic status, less employment participation and poorer health status (Blyth et al., 2001). In 2018 in Australia, the overall cost of persistent pain was estimated to be 139.3 billion and the nation’s third most costly health problem (Pain Australia, 2020). In Tasmania, an island state of Australia with a population of just over half a million people, the persistent pain problem is compounded by an ageing population, increased prevalence of chronic disease, higher lifestyle risk factors, lower educational attainment and workforce participation and higher poverty rates relative to the rest of Australia (Department of Health and Human Services [DHHS], 2018). Although recommendations that persistent pain be assessed and managed with a multimodal, multidisciplinary approach are widely accepted (Gatchel et al., 2007), less than 10% of the Australian pain population accesses multidisciplinary care due to geographical challenges and service availability and access (Pain Australia, 2020). Tasmania, characterised by higher geographical dispersion across rural and remote areas is no exception, with access worsening with remoteness (DHHS, 2018). As the Tasmanian (and Australian) population ages, the need for a skilled health workforce to manage the growing and increasingly complex demands for persistent pain presentations will increase. This need has prompted calls for the development and enhancement of multidisciplinary undergraduate education programs (National Drug and Alcohol Research Centre, 2012; Pain Australia, 2011).